Expectations of youth and parents from drug addiction awareness efforts in Turkey - Sezgin, Deniz; Akçakaya, İbrahim Barbaros (Journal of Dependence, 2019)
Objective: This work was driven by the sense of responsibility and by the aim of providing/raising awareness for the youth regarding drug addiction. In order to raise the awareness of youth within the framework of drug addiction, Republic of Turkey Ministry of Health General Directorate of Health Promotion made 2 spot films which were intended for the youth and 1 spot film related to the “191 Line”; “The Counseling and Support Line for the Fight Against Drugs which addressed a larger target population.Method: The aforementioned 3 spot films were analyzed with the method of focus group analysis, containing the opinions of the intended population regarding the films and the subject at hand.Results: It was seen that negative elements such as fear and death which were used in the public service announcements that are intended to raise awareness in terms of “drug addiction” were not considered as dissuasive from the perspective of teenagers. Moreover, parents do not want studies to be conducted which induces fear and anxiety among themselves and their children. Teenagers and their parents think that the processes which lead the individual towards drug addiction should be clarified and elaborated in a clear manner within the future studies.Conclusion: These individuals expect the related films and studies to contain positive messages regarding the subject and they also expect these works to touch people’s lives, to make contact with the society itself.
Keywords: Drug addiction; youth; family; awareness